Epidemiology of injuries in National Collegiate Athletic Association women's softball: 2014-2015 through 2018-2019 - Veillard, K. L.; Boltz, A. J.; Robison, H. J.; Morris, S. N.; Collins, C. L.; Chandran, A. (Journal of Athletic Training, 2021)
Context: Women's softball athletes account for approximately 9% of all female athletes competing within the National Collegiate Athletic Association (NCAA). Background: Routine surveillance of NCAA women's softball injuries is important for identifying the emerging injury patterns in this sport. Methods: Exposure and injury data collected during competitive seasons in the NCAA Injury Surveillance Program during 2014-2015 through 2018-2019 (5 years) academic years were analyzed. Injury counts, rates, and proportions were used to describe injury characteristics; injury rate ratios (IRRs) were used to examine differential injury rates. Results: The overall injury rate was 3.92 per 1000 athlete exposures. Practice and preseason injury rates increased during 2015/16 through 2018/19. Most injuries were shoulder (15.2%), hand/wrist (11.8%), knee (11.2%), and head/face injuries (11.2%) and were classified as contusions (14.2%), sprains (14.1%), and inflammatory conditions (14.1%). Concussion (6.8%) was the most commonly reported injury, and concussion incidence fluctuated during 2014-2015 through 2018-2019. Summary: Results indicate an increasing trend in practice and preseason injury incidence. Findings also suggest that workload accumulation in the shoulder and the mechanisms of concussion warrant further attention in this population.